The Impact of European Integration on the Stability of Ukrainian Financial Markets - KUCHER, Galyna; GALENKO, Oksana; KAPYRULYA, Mykhaylo; KAPYRULYA, Mykhaylo; KOSTIUK, Viktoria; VOLKOVSKYI, Ievgen (Theoretical and Practical Research in Economic Fields, 2025)
The aim of the study was to analyse the impact of the level of financial openness in the context of European integration on the stability of the financial markets of Ukraine. The research employed correlation, analysis of variance (ANOVA), and regression analysis. The regression model for the foreign exchange market obtained in the study showed that globalization has a significant and negative impact on the hryvnia exchange rate. The regression coefficient for the KOF Globalisation Index was 0.982115, which in the context of the analysis indicated a weakening of the hryvnia against the US dollar. At the same time, a mitigating effect on the exchange rate can be observed due to an increase in foreign trade turnover. The coefficient for this indicator reached -0.556658, which means a strengthening of the hryvnia due to an increase in foreign trade turnover. A statistically significant effect of the Debt-to-GDP ratio, the share of non-cash payments, and the number of commercial banks with foreign capital on consumer price indices was also found. This indicates that the increase in financial openness in the context of European integration can have a destabilizing effect on the money market, which requires decisive government action. The results obtained can be useful for politicians in the process of developing integration strategies, as it will allow considering the potential negative consequences of increasing financial openness and using the benefits .